Eosinophilic esophagitis—an underestimated food allergy? Eosinophile Ösophagitis – Eine unterschätzte Nahrungsmittelallergie? - Hörning, André; Madisch, A. (Die Dermatologie, 2025)
Eosinophilic oesophagitis (EoE) is a chronic T2-inflammatory disease and can be figuratively referred to as atopic dermatitis of the oesophagus. It is an immune-mediated disease caused by food allergens and is histologically defined by eosinophilic infiltration and clinically characterised by symptoms of oesophageal dysfunction. In addition to reducing the currently still considerable diagnostic latency, the focus is on prioritising existing and new treatment options with the aim of ensuring effective patient care with improved quality of life in the long term.
CRIS-Team Scopus Importer:2025-06-06
Keywords: Elimination diet; Eosinophilic infiltration; Esophageal dysfunction; Food allergens; Quality of life